A Cytochrome B5-Like Heme/Steroid Binding Domain Protein, PlCB5L1, Regulates Mycelial Growth, Pathogenicity and Oxidative Stress Tolerance in Peronophythora litchii - Li, Wen; Li, Peng; Zhou, Xiaofan; Situ, Junjian; Lin, Yiming; Qiu, Jiahui; Yuan, Yuling; Xi, Pinggen; Jiang, Zide; Kong, Guanghui (Frontiers in Plant Science, 2021)
As electron transport component, cytochrome b5 is an essential component of the Class II cytochrome P450 monooxygenation system and widely present in animals, plants, and fungi. However, the roles of Cyt-b5 domain proteins in pathogenic oomycetes remain unknown. Peronophythora litchii is an oomycete pathogen that causes litchi downy blight, the most destructive disease of litchi. In this study, we identified a gene, designated PlCB5L1, that encodes a Cyt-b5 domain protein in P. litchii, and characterized its function. PlCB5L1 is highly expressed in the zoospores, cysts, germinated cysts, and during early stages of infection. PlCB5L1 knockout mutants showed reduced growth rate and β-sitosterol utilization. Compared with the wild-type strain, the PlCB5L1 mutants exhibited significantly higher tolerance to SDS and sorbitol, but impaired tolerance to cell wall stress, osmotic stress, and oxidative stress. Further, the expression of genes involved in oxidative stress tolerance, including peroxidase, cytochrome P450 and laccase genes, were down-regulated in PlCB5L1 mutants under oxidative stress. Importantly, we also found that PlCB5L1 is required for the full pathogenicity of P. litchii. This is the first report that a Cyt-b5 domain protein contributes to the development, stress response, and pathogenicity in plant pathogenic oomycetes.